Evaluation study of pedestrian way’s comfort case study : Blang Padang Area, Banda Aceh City / Nanda Ulfa, Irfandi and Cut Dewi - Ulfa, Nanda; Irfandi, Irfandi; Dewi, Cut (2018)
Nowdays, footways or pedestrian wayis one of important public facilities because it is not only providing a connection between place to place, but also considered as a temporary shelter (Indraswara, 2006). As a growing city which survived the 2004 Tsunami Disaster, Banda Aceh has grown rapidly, so has its public facilities, However, based on an innitial observation, inspite of there are several footways available accross the city, only limited numbers are intensively used.In much of Banda Aceh, walking seems to be unpleasant experiences due to lack of comfort and poor facilities. In this regards, this study aims to identify individual problems of street segments by looking at the level of pedestrian's comfort and supporting elements they need in daily uses.This study selected Blang Padang area, one of the most vibrant areas of Banda Aceh and the users were interviewed using semi structured inetrview. In addition to interview, this study employed field observation to record existing physical conditions. The results shows that 85% of pedestrian ways around the study area are inconvenient, uncomfortable and sometimes dangerous to be used.In addition, theexisting condition of pedestrian ways are in minimum condition such as its pavement, safety, vegetation, accessibility, and cleaness; and lack of street furniture facilities. Therefore, based this, some designs are suggested to increase level of comfort in the pedestrian way around Blang Padang and Banda Aceh, so the level of pedestrian way uses can be leveled up.